Resilience, Reorientation, and Reinvention: School Leadership During the Early Months of the COVID-19 Pandemic - McLeod, Scott; Dulsky, Shelley (Frontiers in Education, 2021)
As the COVID-19 pandemic spread rapidly across the globe, many schools struggled to react both quickly and adequately. Schools were one of the most important societal institutions to be affected by the pandemic. However, most school leaders have little to no training in crisis leadership, nor have they dealt with a crisis of this scale and this scope for this long. This article presents our findings from interviews of 43 school organizations around the globe about their responses during the early months of the pandemic. Primary themes from the interviews included an emphasis on vision and values; communication and family-community engagement; staff care, instructional leadership, and organizational capacity-building; equity-oriented leadership practices; and recognition of potential future opportunities. These findings resonate with the larger research literature on crisis leadership and have important implications for school leaders’ future mindsets, behaviors, and support structures during crisis incidents.